Preliminary Phytochemical Screening of Various Extracts for Five Plant Species in Iraqi Kurdistan Region - Masum, Pshtiwan A.; Osw, Peshawa Sh. (Science Journal of University of Zakho, 2016)
Iraqi Kurdistan region is well known for its rich traditional medicinal plants. The present study is a preliminary qualitative phytochemical screening, using ultrasonic technique for extraction through three solvents; petroleum ether, ethyl acetate and aqueous ethanol. The studied plants included Malabaila secacula (root), Muscari longipes (bulb), Crepis sahendi (root), Nepeta trachonitica (aerial part) and Daphne mucronata (aerial part). All studied plants were rich sources for flavonoids and carbohydrates, inversely; alkaloids were absent in both ethyl acetate and aqueous ethanolic extracts, while glycosides, phenolics, tannins, saponins, amino acids and proteins showed various results in the previous two extracts. In addition, phytosterol constituents were present in petroleum ether extracts from all the studied plants except for bulb of Muscari longipes. Phytochemicals diversity suggested that Nepeta trachonitica is the best relative to the other studied species, this will be helpful for further phytochemists and pharmacologists investigations.